Innovation of Processed Baronang Fish as One of The Local Food Products in Gebang Village, Pesawaran - Silvia, Ridha; Dewi, Adjeng Permana; Nurfitriani, Desty; Yudiyanto, Yudiyanto; Wakhidah, Anisatu Z. (Jurnal Biologi Tropis, 2024)
Gebang Pesawaran Village is an area that occupies a coastal area and has quite abundant marine products, but the potential for utilization is less than optimal and there is no food made from any of the existing marine products. This research aims to explore the potential of rabbitfish itself and to create local food products that are losng-lasting but still nutritious in Gebang Pesawaran Village. It is also an effort to create a variety of food dishes that do not only depend on one type of ingredient, but also utilize a variety of food ingredients. The product made in this research was serundeng with coconut and rabbitfish as the basic ingredients, which was named Seronang. The method used in this research is qualitative with a descriptive approach. The results of the research show that the baronang fish serundeng product is a new food innovation in Gebang Village. This product has passed food chemical test analysis and has a nutritional value information label to make it easier for consumers to consume the product. From the results of chemical food tests, it is known that the nutritional content contained in baronang fish serundeng products includes air content of 5.4481%, glucose 6.1474%, fat 32.8965%, carbohydrates 31.8109%, protein 23.6970%, and vitamins 8.8597%.